2019
DOI: 10.3329/medtoday.v31i1.40316
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence Patterns to Anti-diabetic Drugs among Type 2 Diabetic Patients

Abstract: Introduction: The aim of the present study was to evaluate the pattern of medication adherence to anti-diabetic drugs among type 2 diabetic patients at two tertiary level hospitals in Mymensingh. Materials and Methods: An observational, cross sectional study was conducted from January 2016 to June 2016 among patients attending at Endocrine Outpatient Department of the Mymensingh Medical College Hospital and Medicine Outpatient Department of the Community Based Medical College Hospital, after obtaining re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…However, the proportion of females not using the medication is higher than that of the males. This finding is aligned with previous studies conducted in both developing and developed countries such as India [ 17 , 18 ], and the United States [ 16 ], and partly confirms a study conducted in Ethiopia by Araya and colleagues [ 12 ], which found 63.9% of non-use of medication among persons diagnosed of diabetes. There are several possibilities that could account for these sex disparities in medication usage.…”
Section: Discussionsupporting
confidence: 91%
“…However, the proportion of females not using the medication is higher than that of the males. This finding is aligned with previous studies conducted in both developing and developed countries such as India [ 17 , 18 ], and the United States [ 16 ], and partly confirms a study conducted in Ethiopia by Araya and colleagues [ 12 ], which found 63.9% of non-use of medication among persons diagnosed of diabetes. There are several possibilities that could account for these sex disparities in medication usage.…”
Section: Discussionsupporting
confidence: 91%